Leader and peer ethical behavior influences on job embeddedness - Ferreira, A. I. (Journal of Leadership and Organizational Studies, 2017)
Drawing on the social learning theory, the current research proposes that employees learn specific ethical behavior by observing others (leader and peers), thus influencing their job embeddedness. This study examined the mediating and moderating contextual variables in the relationship between ethical leadership and job embeddedness using a sample of 343 employees from 40 different companies. Results revealed that ethical leadership is related to job embeddedness and that perceived supervisor support mediated the influence of ethical leadership on job embeddedness. Also, peer unethical behavior moderated the indirect ethical leadership–job embeddedness relationship at the group level of analysis. Implications of these findings for research and practice are discussed. Specifically, this study proposes that there is a need to select middle managers that are focused on people’s needs and to train and motivate supervisors to support and stimulate their subordinates.